Special skill exercises to develop mechanical movement behavior and the accuracy of Setting skill performance for volleyball players - Yasir, Alaa Muhsun; Hammood, Hussein Srayyih; Sikhe, Husein Sabhan; Khyon, Ansam Yarub (International Journal of Psychosocial Rehabilitation, 2020)
The intentional research sample consisted of the players of the Specialized Center for the Care of Sports Talent for Volleyball at the Ministry of Youth and Sports in Baghdad. They reached (6) athletes. The researchers used special skill exercises to develop mechanical movement behavior and the accuracy of the performance of the preparation skill. The kinetic analysis program (Kinovea) was also used, in order to extract the kinematic variables of the setting skill. The accuracy test of numbers close to the network was used to measure the accuracy of the setting skill of the setting players in volleyball. The aim of the research was to identify the effect of special skill exercises on the mechanical variables (as mechanical movement behavior) and the accuracy of the setting skill of the setting players In volleyball. The sample members were characterized by the highest accuracy of numbers, and mechanical variables (as mechanical behavior) improved as a result of the effect of special skill exercises.